Self-Efficacy, Mindfulness, and Burnout among Phd Students - Rimsha Urooj; Dr. Shagufta Bibi; Dr. Muhammad Luqman Khan (Research Journal of Psychology, 2025)
The purpose of the present study was to measure the relationship between Self-efficacy, mindfulness, and burnout among PhD students. To examine the correlation between Self-efficacy, Burnout, and Mindfulness. There was a significant correlation between self-efficacy and mindfulness, self-efficacy and academic burnout, mindfulness and Academic burnout in PhD students. The study involved 250 students, (123 Male and 127 Female), from various government and private universities, in Pakistan. Using a cross-sectional correlation research design. The research utilized three key psychological measures: The General Self-Efficacy Scale (GSES), a 10-item measure, Mindfulness Attention Awareness Scale (MAAS), a 15-item measure; and Maslach Burnout Inventory-General Survey for Students (MBI-GSS), a 22-item measure. The findings revealed significant associations among all variables under investigation. Furthermore, multiple regression analysis identified self-efficacy, and mindfulness as significant predictors of Academic burnout. These results suggest that incorporating self-efficacy, and mindfulness support into educational programs may enhance students, mental health and overall well-being.